2003
DOI: 10.1136/jcp.56.11.811
|View full text |Cite
|
Sign up to set email alerts
|

The Scotland and Newcastle epidemiological study of Hodgkin's disease: impact of histopathological review and EBV status on incidence estimates

Abstract: Aims: The epidemiological and pathological features of Hodgkin lymphoma (HL) are complex. The Epstein-Barr virus (EBV) is consistently associated with a proportion of cases, and these cases are thought to represent a distinct aetiological subgroup of HL. The aim of the present analysis was to determine the age and sex specific incidence of EBV associated and non-associated HL, analysed separately, using data derived from a population based study-the Scotland and Newcastle epidemiological study of Hodgkin's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 30 publications
7
79
3
Order By: Relevance
“…This is in concurrence with the study by Sudipta Chakrabarti et al [4], Jarrett et al [5] and Bidyut Krishna et al [6]. This study is discordance with the study conducted by Neelam Siddiqui et al [7], which showed unimodal distribution.…”
Section: Discussioncontrasting
confidence: 56%
“…This is in concurrence with the study by Sudipta Chakrabarti et al [4], Jarrett et al [5] and Bidyut Krishna et al [6]. This study is discordance with the study conducted by Neelam Siddiqui et al [7], which showed unimodal distribution.…”
Section: Discussioncontrasting
confidence: 56%
“…-Europe [8,13,[31][32][33][34][35][36][37][38][39][40][41]; between 27% of cases in Sweden [41] and 56% of cases in Italy [13] were positive, with a higher rate in two reports: 79% in Switzerland [31] and 91% in Greece [8] -USA [12,[42][43][44]: between 25% and 65% of cases were positive -Australia [8]: a high frequency of positive cases (69%).…”
Section: Discussionmentioning
confidence: 99%
“…These patients also exhibited a reduced survival in comparison to EBV-negative patients 8 . Recently, Ganhdi et al 3 and Jarrett et al [9][10][11] indicated that the decline in EBV-specific cellular immunity that occurs with age may contribute to the development of EBV-positive CHL in older patients. These conclusions also reinforce the recognition of senile EBV + B cell LPDs as a continuous spectrum of EBV + CHL.…”
Section: Ebv-associated Classical Hodgkin Lym-phoma and Ebv-associatementioning
confidence: 99%